Diversity and factors affecting habitat utilization of birds in Lumbini Sacred Garden, Nepal - Gyawali, Asmita; Bhattarai, Binod; Bhattarai, Bishnu Prasad (FORESTRY: Journal of Institute of Forestry, Nepal, 2025)
Lumbini in Rupandehi District in southern Nepal is not only a culturally significant site but also rich in biodiversity with diverse habitats such as wetlands, forests and farmlands. It lies along the Central Asian Flyway, which makes it an important stopover for many resident and migratory bird species. The study was conducted in the Lumbini Sacred Garden (LSG) of Rupandehi District, to explore the bird diversity and habitat utilization. For the bird survey, the point count method was used. Altogether 994 individuals belonging to 111 species, representing 15 orders and 41 families, were recorded, in which 79 species were resident and 32 were winter visitor. Passeriformes (48 species) were found to be the dominant order. The Shannon diversity index in LSG was 3.686, whereas the Simpson diversity index was 0.9721, and the evenness value was 0.8867. The habitat utilization rate was higher, with the utilization rate of 0.46, than in grassland and wetland. Carnivores did not show significant relationship with the habitat type, whereas frugivores were associated with forest, herbivores were strongly associated with wetlands, insectivores and omnivores showed significant relationship with forest and grassland habitats. Feeding guild of the species also drives the habitat utilization pattern of the avifauna. The presence of people and livestock had a significant effect on the diversity and abundance of birds. This study suggests that humans are the key factors for degrading the habitat, which negatively impacts the distribution, diversity and abundance of birds in the reservoirs, which helps to develop climate change mitigation strategies and sustainable forest management policies.